SUS-PDAT in Applied Science Learning: Making Red Oncom as a Food Innovation for a Healthy and Prosperous Life Without Hunger - Fitriyah*, Isnanik Juni; Aprilia, Septi; Manasikana, Oktaffi Arinna; Muzzazinah, Muzzazinah (Universitas Syiah Kuala, 2024)
Innovation in the food sector to support national development in alleviating hunger and creating a healthy and prosperous life can be carried out in various fields, one of which is education. The aim of the implementation of SUS-PDAT in this applied IPA learning is to give practical experience to students in the process of making red oncoms. This research uses a qualitative approach with a descriptive type. Data collection is carried out through the study of literature from various sources, including national and international journals relevant to research topics. Research shows that by introducing food innovations like red oncom to students, it can raise awareness of the importance of healthy and sustainable food consumption in society. Besides, this learning can also be a source of inspiration for the younger generation to engage in the innovative and environmentally friendly food industry of the future. Therefore, red oncom is included in healthy food with affordable economic value. It is hoped that the red oncom innovation which has an umami taste can help the government in sustainable development for a healthy and healthy life without hunger.